Kuzmány’s hymn “Glory to the Noble” (Sketches for interpretation) - Lomenčík, Július (Napredak, 2026)
The aim of this article is to use interpretative sketches to discover the humanistic semantics of Kuzmány’s hymn “Glory to the Noble” which is, from the philosophical perspective, a classic example of Hegel’s dialectic triad. The conclusion points to the still valid ideological message of this hymn (today known under the title “Who Burns for Truth”) in the promotion of truth, freedom and equality.